Community violence and African American male health outcomes: An integrative review of literature. (19th June 2020) - Thomas, Paris; Duffrin, Melani; Duffrin, Christopher; Mazurek, Kathryn; Clay, Shondra L.; Hodges, Terence
Abstract: Community violence exposure is essential when considering African American male adult health outcomes. This integrative review of literature is guided by the research questions: (a) How has community violence been measured in African American male adults? and (b) What impact does community violence have on African America male health outcomes? This study synthesises eight current articles identified by the search terms—community violence, impact, African Americans, care, and men. Of the eight identified articles, there were quantitative ( n = 5), qualitative ( n = 1) and mixed methods ( n = 2). Findings indicate a wide array of screening tools for violent experiences and highlight the potential negative impacts of violence in communities; however, literature regarding strategies for identification and treatment of psychosocial and physical health status of African American male adults experiencing direct and indirect community violence remains limited. Further work in clinical care and community health settings related to violence is warranted.